Around the goal: examining the effect of the first goal on the second goal in soccer using survival analysis methods - Nevo, D.; Ritov, Y. (Journal of Quantitative Analysis in Sports, 2013)
In this paper we apply survival techniques to soccer data, treating a goal scoring as the event of interest. It specifically concerns the relationship between the time of the first goal in the game and the time of the second goal. In order to do so, the relevant survival analysis concepts are readjusted to fit the problem and a Cox model is developed for the hazard function. Time dependent covariates and a frailty term are also considered. We also use a reliable propensity score to summarize the pre-game covariates. The conclusions derived from the results are that a first goal occurrence could either expedite or impede the next goal scoring, depending on the time it was scored. Moreover, once a goal is scored, another goal scoring becomes more and more likely as the game progresses. Furthermore, the first goal effect is the same whether the goal was scored or conceded.